TITIK PERSINGGUNGAN ANTARA HUKUM DAN MORAL DALAM TINDAK PIDANA KORUPSI MENURUT PERSPEKTIF NEO POSITIVISME HUKUM - Rahman, Fathor (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2024)
The issue of corruption is a moral issue, so in this regard it can be said that a person who commits the crime of corruption is experiencing a process of moral decadence in himself. This study focuses on the two poles of legal philosophy between Legal Positivism and Legal Neo-Positivism. It is believed that moral values can be seen as the deepest sediment in the formation of norms, which is then expected to be able to find legal entities to answer the challenges of corruption problems in Indonesia through the spirit of moral improvement. The purpose of this paper is to examine a treatise on the thinking of a philosophical figure influenced by the school of Legal Positivism, namely H.L.A Hart, who chose to renew from pure positivism legal thinking, which in the end he identified the nature of law there is a mutual relationship between law and morals, although it is not absolute. The method of this writing is to use normative legal research. The results showed that Hart's thinking regarding the reflection of the relationship between law and morals does not always have a diametrical separation between law and morals. Hart indirectly recognizes that law, justice, and morals have a very close relationship, with the open texture of law. The open nature of the law to legal factors when it comes to criminal acts of corruption is not seen from the consideration of legal sanctions alone but there are natural considerations that cause moral disgrace that damage the joints of national life. The sanctions given are not only legal sanctions but also moral sanctions, which are not only used as a deterrent effect but a lesson for them to be afraid of committing corruption. Key words: Corruption, Law, Moral, Neo Legal Positivism